ln(x+2)-ln(x)=4

Simple and best practice solution for ln(x+2)-ln(x)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x+2)-ln(x)=4 equation:


Simplifying
ln(x + 2) + -1ln(x) = 4

Reorder the terms:
ln(2 + x) + -1ln(x) = 4
(2 * ln + x * ln) + -1ln(x) = 4
(2ln + lnx) + -1ln(x) = 4

Multiply ln * x
2ln + lnx + -1lnx = 4

Combine like terms: lnx + -1lnx = 0
2ln + 0 = 4
2ln = 4

Solving
2ln = 4

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Divide each side by '2n'.
l = 2n-1

Simplifying
l = 2n-1

See similar equations:

| x^2+57x-630=0 | | -8/x=7 | | 36-11x=13+12x | | logx^83=3 | | 9x-4*20=5*20 | | 8/5y-7=49 | | (x+20)0.75=x | | f(x)=1/sen^2x | | 120+120+120+120+x=720 | | 23w+15-5+2w=5 | | 78+42+42+x=360 | | 39+7m=95 | | 0.2p+2.2+2.2p=4.36 | | 3x-10+3x-10+52=180 | | 7(3-4x)=-63 | | 1/2x(x-3)=27 | | 3x-10+3x-10=52 | | (9x-5)+(4x+29)=26 | | 15n-65=130 | | 3x-10y=-11 | | Ntimes-5=-155 | | -8m^3(3m^2)=0 | | 1/2log13.28 | | 7(3+4x)=-203 | | 3+2k=15 | | X+x-21=87 | | 2.35e^2x=947 | | 22-8/-2 | | f(1)=2x-1 | | 5[3(x+4)-2(1-x)]-x-15=14x+75 | | 1/2=-3/5y-2/3 | | (7x+11)+(16x-38)=77 |

Equations solver categories